'I wonder what you know … ' teachers designing requests for factual information. (October 2016) - Houen, Sandy; Danby, Susan; Farrell, Ann; Thorpe, Karen
Abstract: Optimizing the quality of early childhood education (ECE) is an international policy priority. Teacher-child interactions have been identified as the strongest indicator of quality and most potent predictor of child outcomes. This paper presents ethnomethodological and conversation analysis of an interaction between an early childhood educator with two children as they engage in Web-searching. Analyses shows that question design can elicit qualitatively different responses with regard to sustained interactions. Understanding the design of teacher questions has pedagogic implications for the work of the teacher and for the broader quality agenda in early childhood education. Highlights: The design of teachers' requests for factual information affects children's responses. 'I wonder … ' provides teachers with a strategy to question in a soft implicit way. 'I wonder … ' invite children's responses. 'I wonder … ' seemed to remove the 'test' characteristic of teacher questioning.